Prediction of Short-Term Outcome after Primary Percutaneous Coronary Intervention by CADILLAC Risk Score (Bangladesh Heart Journal, 2023)
Introduction: The CADILLAC risk score (CRS) has been developed and validated in the context of primary PCI as a reperfusion strategy for accurate risk stratification. Patients with low CRS have better outcome than those with intermediate to high CRS. However, further studies are needed to validate this score in our population.Aim of the study: The present study was conducted to predict the short-term outcome after primary percutaneous coronary intervention (pPCI) by CRS. Method: This prospective observational study was conducted at the National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from March, 2019 to August, 2020, on 62 patients with two equally divided groups based on CRS: Group I with score 0-2 and Group II with e” 3. The score was calculated by summation of points gathered from each component of the score. Bleeding events, vascular access site complication, heart failure, cardiogenic shock, significant arrhythmia, major adverse cardiovascular and cerebrovascular events (MACCE), were observed during hospital stay and at 30- day follow up.Result: Mean CRS of the groups were 0.45±0.85 and 4.71±1.74 respectively. Overall adverse outcome, both in-hospital and 30-day, were significantly higher in group II (12.9%vs.35%, p=0.003 and 0vs.22.6%, p=0.001 respectively). Heart failure (22.6%vs.6.5%, p=0.04; 19.4%vs.0, p=0.01) and MACCE (19.3%vs.3.2%, P=0.04; 16.1vs.0%, p=0.02) were significant during hospital stay and at 30-day follow up. Bleeding events (12.9%vs.0, p=0.03) and significant arrhythmia (6.5%vs.0, p=0.04) were significant during hospital stay. Length of hospital stay was also significantly shorter in group I (d”3days: 74.2%vs.35.5%; p= 0.01). The components of CRS except post-PCI TIMI (Thrombolysis in myocardial infarction) flow, intermediate to high CRS, male gender, diabetes mellitus, hypertension, were significant in univariate regression analysis. Moderate to high CRS (in-hospital and 30-day), left ventricular ejection fraction< 40% (inhospital), triple vessel disease (30-day) were significant in multivariate analysis. ROC curve analysis showed, area under the curve for CRS was 0.745 (95% CI: 0.616- 0.874; p=0.001). CRSe”3 predicted in-hospital outcome after pPCI with sensitivity and specificity of 35.5% and 87%, respectively.Conclusion: In the setting of pPCI, low CRS is associated with better in-hospital outcome in comparison to intermediate to high CRS. Also, in comparison to intermediate to high CRS, low CRS is associated with better 30-day outcome after pPCI, However, for prediction of adverse short-term outcome after pPCI, CRS has got relatively low sensitivity and high specificity.Bangladesh Heart Journal 2023; 38(1): 32-37